Genome-Wide Association Study Points to Novel Locus for Gilles de la Tourette Syndrome - The PGC TS Working Group; The TSAICG; The TSGeneSEE Initiative; The EMTICS Collaborative Group; The TS-EUROTRAIN Network; The TIC Genetics Collaborative Group (Elsevier Inc., 2024)
Background: Tourette syndrome (TS) is a childhood-onset neurodevelopmental disorder of complex genetic architecture and is characterized by multiple motor tics and at least one vocal tic persisting for more than 1 year. Methods: We performed a genome-wide meta-analysis integrating a novel TS cohort with previously published data, resulting in a sample size of 6133 individuals with TS and 13,565 ancestry-matched control participants. Results: We identified a genome-wide significant locus on chromosome 5q15. Integration of expression quantitative trait locus, Hi-C (high-throughput chromosome conformation capture), and genome-wide association study data implicated the NR2F1 gene and associated long noncoding RNAs within the 5q15 locus. Heritability partitioning identified statistically significant enrichment in brain tissue histone marks, while polygenic risk scoring of brain volume data identified statistically significant associations with right and left thalamus volumes and right putamen volume. Conclusions: Our work presents novel insights into the neurobiology of TS, thereby opening up new directions for future studies.
Keywords: GWAS; Meta-analysis; NR2F1; Tourette syndrome; Taverne; Biological Psychiatry